Association of metabolic syndrome and chronic periodontitis in colombians (2016)
Background: Metabolic syndrome (MetS) is a common chronic condition that increases the cardiovascular disease risk and is also linked to periodontitis. The study aim was to determine if a relationship exists between MetS and chronic periodontitis in adult Colombians. Methods: Participants were 220 healthy-gingivitis subjects and 431 periodontitis patients coming from the three largest Colombian cities. Periodontal status and MetS were determined in subjects. Univariate analysis and odds ratio were calculated within the 95 % confidence intervals and chi2 test compared the groups. Variables were compared among the clinical periodontal groups and MetS by Wilcoxon and multivariate analysis, and logistic regression was performed for MetS and periodontitis. Results: MetS had higher prevalence in periodontitis group (6.3 %) versus controls (3.2 %). In multivariate analysis, periodontitis was associated with MetS (adjusted OR = 2.72, 95 % CI 1.09–6.79), glucose intolerance with another component of MetS (adjusted OR = 1.78, 1.16 to 2.72), glucose resistance (adjusted OR = 11.46, 95 % CI 1.41–92.88), smoking (OR = 1.72, 95 % CI 1.09–2.71), and city of origin (2.69, 95 % CI 1.79–4.04). Conclusion: The study confirmed the positive association between MetS and periodontitis, being glucose sensitivity the strongly associated component. Clinical relevance: MetS must be taken into account by the dentist when evaluating risk factors for periodontitis, being useful for dentists to evaluate glycemia, lipidic profile, central obesity, and high blood pressure in patients. Interdisciplinary treatment must be recommended when a patient with MetS and periodontitis is being treated